2019
DOI: 10.1063/1.5092542
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of drag characteristics of ventilated supercavitating vehicles with different body shapes

Abstract: This paper presents an experimental investigation on drag characteristics and flow physics of ventilated supercavitating objects with different body shapes. The test model consists of a disk-type cavitator with two different forebodies (slender and blunt shape) and three different rear bodies (flat, shrinkage, and expanded shape). Experiments are conducted in a cavitation tunnel of the Chungnam National University. First, the drag forces acting on different body-combinations in fully wetted conditions are meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The evolution of supercavitation flow involves multiple processes of closure and separation [8]. Jiang et al [9], Mohammadrahimi et al [10], and Shao et al [11] independently examined supercavitation vehicle models with different head shapes and concluded that the cone-shaped head design is desirable to form the stable supercavitation. Based on their work, Pham et al [12] tested several models with conical heads of various angles and found that smaller cone angles contribute to the occurrence of supercavitation.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of supercavitation flow involves multiple processes of closure and separation [8]. Jiang et al [9], Mohammadrahimi et al [10], and Shao et al [11] independently examined supercavitation vehicle models with different head shapes and concluded that the cone-shaped head design is desirable to form the stable supercavitation. Based on their work, Pham et al [12] tested several models with conical heads of various angles and found that smaller cone angles contribute to the occurrence of supercavitation.…”
Section: Introductionmentioning
confidence: 99%
“…Many years ago, researchers carried out a series of scientific investigations into the motion characteristics of bubbles in liquids (Bhaga and Weber 1981, Logvinovitch 1969, Clift et al 1978, Coutanceau and Thizon 1981, Lauer et al 2012, and determined the dynamic behaviour of bubbles in different viscous liquids. Through further research, it was found that the ventilated cavity covering the surface of an underwater vehicle can effectively reduce the travelling resistance (Jiang et al 2019, Zou et al 2021, which provides a new direction of research into underwater vehicles. Kim and Kim (2015) further studied the hydrodynamic characteristics of ventilated supercavities and established a dynamic model for vehicles that produced this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…H. Forouzani et al [6] simulated the supercavitation dynamics and planing force through two mathematical models based on experiments and established the motion equation of a supercavitating projectile. Jiang et al [7] investigated the drag characteristics and flow physics of ventilated supercavitating objects with two different forebodies and three different rear bodies through cavitation tunnel experiments.…”
Section: Introductionmentioning
confidence: 99%